GATA3 expression in clear cell adenocarcinoma of the lower urinary tract: a potential diagnostic pitfall - Mahmut Akgul; Robert Humble; Abdullah Osme; Servet Yuce; Elif N. Kocak; Parisa Najafzadeh; Ankur Sangoi; Niharika Pattnaik; Sourav Mishra; Shivani Sharma; Nada Shaker; Seema Kaushal; et al. (BMC, 2022)
Highlights Clear cell adenocarcinoma of the lower urinary tract is rare, with heterogenous morphology. GATA3 expression can be seen in these tumors, causing diagnostic challenge in the urinary tract or in the metastatic setting. Along with morphologic clues, immunohistochemical panel of PAX8, GATA3, and p63 might be useful to distinguish these tumors from urothelial carcinoma.